(untitled) (Journal of Human Sciences, 2023)
The story is a self-contained art that belongs to the narrative arts at the level of form and structure. It studies literature, the social environment, and disparate events. It is an authentic art, and an honest and transparent image of the human experience in different times and places, and a rich source of knowledge and pleasure in seeing the ins and outs of the human psyche. , and its secrets and its struggle with life and society within a coherent artistic framework that guarantees the continuity of human participation, especially since it is one of the most prominent and circulated texts known to the young before the old, and from this standpoint came the idea of this scientific paper and we tried through it to focus on one of the most important types The tale, which is the tales spoken by the animal, being the most influential on the child’s psyche Since we have focused our discussion here on education programs directed at the child in the early stages of his formation and education.